2004
DOI: 10.1016/j.seizure.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal memory functioning following right anterior temporal lobectomy: a meta-analytic review

Abstract: Overall, the collective findings demonstrate the inability of the current research to provide any consistent evidence as to the nature of nonverbal memory outcome following RATL. Problems with nonverbal memory measures are discussed and suggestions for future research are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“…The findings of the current study also underscore that there is still the need to find a more precise neuropsychological marker of right hippocampal integrity [53][54][55][56].…”
Section: Discussionsupporting
confidence: 54%
“…The findings of the current study also underscore that there is still the need to find a more precise neuropsychological marker of right hippocampal integrity [53][54][55][56].…”
Section: Discussionsupporting
confidence: 54%
“…However, contrary to our expectations, abstract shapes were not associated with a significant right lateralization of this component. Previous clinical studies have also demonstrated that left-lateralization of memory for verbal material is more easily observed than the right-lateralization of memory for non-verbal stimuli (Boucher et al, 2015; Lee et al, 2002; Vaz, 2004; Vingerhoets et al, 2006). Nevertheless, a study using functional near-infrared spectroscopy during a recognition task with abstract shapes has recently reported a right-lateralization of the repetition effect over the right ventrolateral prefrontal cortex (Sanefuji et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…A major reason for this approach is that systematic effects of surgery are mostly found only for verbal memory after left temporal lobe surgery. 42,44,48 However, left and right mesial structures appear to provide highly redundant and compensatory functions in verbal memory processing. 17 Accordingly, it can be observed that nonverbal memory may be sacrificed in favor of verbal memory 20 and that material-specific impairments in TLE are less likely in the presence of generally reduced mental capacities.…”
Section: Discussionmentioning
confidence: 99%